Women Farmers’ Knowledge and Practices on Organic Farming - Goswami, Pallab; Noman, Md Rubayet Al Ferdous; Huda, Saiful (Research in Agriculture Livestock and Fisheries, 2021)
The main purpose of the study was to investigate the knowledge and practices of women farmers on organic farming. The study was conducted in two union of Nilphamari Sadar upazila namely Lakshmi Chap and Palashbari under Nilphamari district. Ninety-two (92) women farmers were randomly selected as sample from an updated list of 120 women farmers. Data were collected by a pre-tested interview schedule during 1st to 30th October 2020. Simple and direct questions with different appropriate scales were used to obtain information. Descriptive statistics, correlation and multiple regression analysis was used for the present study. Majority of the respondents know about rotating crops, using different wastes, composting, limiting the use of synthetic/ chemical fertilizers, trap method, and mulching as part of organic farming practices. Majority of the respondents opined that they were practicing more than once „Using organic fertilizer‟, „using plant waste‟, and „using kitchen waste‟ for the last 12 months. Slightly above four-fifths (83.7 percent) of the women farmers had medium practices on organic farming, while 14.1 percent women farmers had high practices on organic farming, and only 2.2 percent women farmers had low practices on organic farming. Thus, a proportion of 85.9 percent of the women farmers low to medium practices on organic farming. Correlation analysis indicated that among nine socio-economic profile educational qualifications, farm holding, training received, extension media contact and innovativeness of women farmers had significant positive relationship with their practices on organic farming. However, age, organic farming experience, annual family income and cosmopoliteness had no significant positive relationship with their practices on organic farming. Regression analysis indicated that education qualification, farm holding, extension media contact, and innovativeness of the respondents had significant positive contribution with their practices on organic farming. Res. Agric., Livest. Fish.8(1): 41-50, April 2021